2007
DOI: 10.1097/mlg.0b013e3180959e38
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Phonation Threshold Flow and Pressure by Abducting Excised Larynges

Abstract: Results showed phonation threshold flow to be more sensitive to posterior glottal width changes than phonation threshold pressure. Therefore, phonation threshold flow could be a more effective indicator than phonation threshold pressure for those vocal diseases related to abduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 17 publications
5
43
0
Order By: Relevance
“…Because the glottal airflow can be easily noninvasively measured, it was suggested that PTF may be more practical for clinical vocal disease assessment. Experimental measurements on excised larynx setups ͑Verdolini et Hottinger et al, 2007͒ andphysical models ͑Titze et al, 1995;Chan and Titze, 2006͒ further confirmed the potential value of these phonation critical conditions on vocal disease assessment.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Because the glottal airflow can be easily noninvasively measured, it was suggested that PTF may be more practical for clinical vocal disease assessment. Experimental measurements on excised larynx setups ͑Verdolini et Hottinger et al, 2007͒ andphysical models ͑Titze et al, 1995;Chan and Titze, 2006͒ further confirmed the potential value of these phonation critical conditions on vocal disease assessment.…”
Section: Introductionsupporting
confidence: 61%
“…Then, in Sec. III, the PTP and PTF predicted by the modified onemass model are compared with experimental data reported by Chan andTitze ͑2006͒ andHottinger et al ͑2007͒. At last, we draw our conclusion.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…When a polyp or nodule is present, the glottal closure is limited, thus increasing air leakage during phonation and resulting in higher-than-normal airflow measurements. 12 Previous experiments using excised canine larynges have shown PTF to increase with the size of a posterior glottal gap, 13 vocal fold elongation, 14 and surface dehydration. 15 Hottinger et al 13 determined that PTF is more sensitive than PTP to changes in posterior glottal width, demonstrating the potential value of the flow parameter in evaluating disorders that are characterized by glottal insufficiency.…”
Section: Introductionmentioning
confidence: 98%
“…Amongst others, work has been carried out with a strong inclination towards fluid dynamics. This includes studies investigating (a) pressure-flow relationships (Alipour et al, 1997;Hottinger et al, 2007); (b) glottal resistance Alipour and Jaiswal, 2009) and glottal efficiency (Titze, 1988); (c) velocity fields within the glottis using particle imaging velocimetry (which in simple terms corresponds to turbulence analysis) ; (d) the dependency of f o on subglottal pressure (Solomon et al, 1994;Alipour and Scherer, 2007;Alipour and Jaiswal, 2008); and (e) the relationship between subglottal pressure and non-linear dynamics of laryngeal voice production (defining the phonation instability pressure, PIP) (Jiang and Titze, 1993;Jiang et al, 2003). Further research emphasis has been directed towards connecting vocal fold motion and geometry with the acoustic signal produced: this includes, amongst others, studies investigating (a) nonlinear dynamics in relation to glottal geometry (vocal fold adduction and/or elongation) (Berry et al, 1996;Jiang et al, 2003) and vocal fold asymmetry (Giovanni et al, 1999); (b) the importance of tissue properties on phonatory characteristics (Chan and Titze, 1999;Alipour et al, 2011); (c) mucosal wave propagation on the vocal folds (Kusuyama et al, 2001;Jiang et al, 2008); and (d) the mechanical forces applying on the vocal folds during phonation (Verdolini et al, 1998;Jiang et al, 2001b;Bakhshaee et al, 2013).…”
Section: Application Of Excised Larynx Experimentation To Human Voicementioning
confidence: 99%